Effectiveness of Video-Guided Birth Ball Exercises on Reducing Back Pain in the Third Trimester of Pregnancy - Made Fitri Yuliandari; I Putu Praja Santika Abadi; Komang Dedi Juliawan (Midwifery Department, Poltekkes Kemenkes Denpasar, Indonesia, 2026)
Pregnancy can cause changes that lead to discomfort for expectant mothers. One of the common complaints experienced by pregnant women is lower back pain. This study was conducted at Ayrin Mom and Baby Care with the aim of identifying differences in the intensity of lower back pain among third trimester pregnant women before and after following instruction in the usage of a birth ball through video media. This research employed a pre-experimental design using one-group pretest-posttest approach. The implementation took place from March to April 2025. The intervention, consisting of 30-minute sessions, was carried out twice a week for four weeks. The sample consisted of 32 participants. A non-probability sampling technique was used with purposive sampling. The results showed that the average lower back pain intensity before the birth ball training was 5.19, and after the training, it decreased to 1.84. Statistical analysis showed that the p-value was 0.000 < 0.05, indicating a significant difference in the intensity of lower back pain among third trimester pregnant women before and after the birth ball training with video media at Ayrin Mom and Baby Care. Pregnant women are encouraged to use birth ball as a means of support and to alleviate lower back pain.